2016
DOI: 10.1007/s10096-016-2618-8
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Seasonal trend and clinical presentation of Bacillus cereus bloodstream infection: association with summer and indwelling catheter

Abstract: Bacillus cereus, an opportunistic pathogen, can cause fatal infection. However, B. cereus bloodstream infections (BSIs) have not been well characterised. From 2008 to 2013, B. cereus isolates from all of the specimens and patients with B. cereus BSIs were identified. Environmental samples were collected to detect B. cereus contamination. We also characterised the clinical presentation of B. cereus BSI through analyses of risk factors for BSI and mortality. A total of 143 clinical B. cereus isolates was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…It was reported that BSI by Bacillus cereus had a seasonal tendency with increased risk of infection during the summer [ 13 ]. Our data showed that S. pneumoniae was more often isolated in winter while K. pneumoniae, P. aeruginosa, A. baumanni, and E. cloacae were most prevalent in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that BSI by Bacillus cereus had a seasonal tendency with increased risk of infection during the summer [ 13 ]. Our data showed that S. pneumoniae was more often isolated in winter while K. pneumoniae, P. aeruginosa, A. baumanni, and E. cloacae were most prevalent in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of B. cereus gastroenteritis were reported [59À61]. Interestingly, the numbers of patients with B. cereus bloodstream infections were higher in summer, and the source was urinary catheters [62]. Meanwhile, women with a month of conception during the summer (OR 1.22, 95% credible interval [CrI] 0.89À1.65) also had higher incidences of preeclampsia, but those who delivered during winter (OR 3.33, 95% CrI 0.31À35.48) had higher incidences of eclampsia in both the northern and southern hemispheres [63].…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al . report 20% mortality among patients with B.cereus BSI [ 28 ]. Mortality rate of B.cereus bacteremia is higher in neonates compared to adults [ 29 ].Patients with prosthetic valve experience higher morbidity and mortality compared to those with native valve [ 22 ].…”
Section: Discussionmentioning
confidence: 99%